Discourses of revolutionary subject in contemporary Marxism - Makris, Spiros (Theoria and Praxis: International Journal of Interdisciplinary Thought, 2015)
While within the framework of a New Socialist Strategy, the issue of communism has been the subject of a comprehensive debate among the most pioneering thinkers of contemporary Marxism, the equally critical issue of revolution and anti-capitalist struggles has not yet entered the heart of Marxistinfluenced analysis of the late capitalism. This sounds like a paradox because it can’t be properly understood how the transition to a communist society will take place, without prior political hegemonic articulatory discursive strategy of rupture with capitalism. From this angle, we will attempt in the present article to constitute the conditions of a (post) Marxist dialogue on revolution, revolutionary subject and anti-capitalism in the era of neo-liberal globalization through Ernesto Laclau and Chantal Mouffe’s oeuvre. For this purpose, we will take into account the relevant projects of important contemporary Marxist theorists as the well-known neo-Marxist geographer and anthropologist David Harvey; the Marxist-oriented sociologist and philosopher John Holloway; and last but not least the famous post-modern political philosophers Michael Hardt and Antonio Negri.